Ultrashort pulse generation with MXene Ti3C2Tx embedded in PVA and deposited onto D-shaped fiber - Jafry, A.A.A. (Elsevier Ltd, 2021)
A two-dimensional ternary metal carbide or/and nitride known as MXene, own countless merits in terms of electronic and optical properties. Owning to its fast optical-switching capability, strong saturable absorption, good optical damage tolerant, and gapless materials, it attracts a bunch of research efforts in an ultrafast photonics application. Here, the development of MXene-based SA devices for ultrafast laser in an erbium-doped fiber laser (EDFL) cavity was demonstrated. Two MXene Ti3C2Tx-based SAs were prepared, which were a thin film of MXene (MXene-film) and MXene deposited onto D-shaped fiber (MXene-DS), both revealed good nonlinear transmittance properties. The selective etching was used to provide a high-quality MXene powder, and the solution-casting method produced liquid MXene, which was dried to form a thin-film structure, and the liquid MXene was deposited onto the D-shaped fiber structure. The MXene-film and MXene-DS own a modulation depth of 1.22 and 3, respectively. Later, both SA devices were incorporated into an EDFL cavity, and MXene-film initiated mode-locked (ML) at the low threshold pump of 44 mW, while MXene-DS produce ML at the pump power of 90 mW. The MXene-film generates a 3.64 ps ML with a pulse energy of 6.03 nJ, separately, MXene-DS initiates a 4.6 ps ML with a pulse energy of 7.69 nJ, highest ever reported among MXene-based SA. This demonstration provides a pathway toward high-energy mode-locking applications in the future. Â© 2020 Elsevier Ltd